2022
DOI: 10.23889/ijpds.v6i3.1705
|View full text |Cite
|
Sign up to set email alerts
|

Data linkage can reduce the burden and increase the opportunities in the implementation of Value-Based Health Care policy: a study in patients with ulcerative colitis (PROUD-UC Study)

Abstract: IntroductionHealthcare systems face rising demand and unsustainable cost pressures. In response, health policymakers are adopting Value-Based Health Care (VBHC), targeting available resources to achieve the best possible patient outcomes at the lowest possible cost and actively disinvesting in care of low-value. This requires the evaluation of longitudinal clinical and patient reported outcome measures (PROMs) at an individual-level and population-scale, which can create significant data challenges. Achieving … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 15 publications
0
1
0
Order By: Relevance
“…Research has already shown that collaboration between different healthcare providers is a challenge in the current Dutch healthcare system, but that the development of a care chain with regional collaboration does improve both clinical and patient-reported outcomes [ 26 ]. Moreover, it is beneficial to collaborate with primary care partners, as they collect relevant outcome data that are part of VBHC standard outcome sets [ 27 ]. This suggests that VI teams should give more attention to collaboration with network partners over the full cycle of care to further improve value for patients.…”
Section: Discussionmentioning
confidence: 99%
“…Research has already shown that collaboration between different healthcare providers is a challenge in the current Dutch healthcare system, but that the development of a care chain with regional collaboration does improve both clinical and patient-reported outcomes [ 26 ]. Moreover, it is beneficial to collaborate with primary care partners, as they collect relevant outcome data that are part of VBHC standard outcome sets [ 27 ]. This suggests that VI teams should give more attention to collaboration with network partners over the full cycle of care to further improve value for patients.…”
Section: Discussionmentioning
confidence: 99%